Stanford neuromodulation therapy for treatment-resistant depression: a systematic review - Lan, Xian-Jun; Cai, Dong-Bin; Liu, Qi-Man; Qin, Zhen-Juan; Pridmore, Saxby; Zheng, Wei; Xiang, Yu-Tao (Frontiers in Psychiatry, 2023)
Objective: This systematic review of randomized controlled studies (RCTs) and observational studies evaluated the efficacy and safety of stanford neuromodulation therapy (SNT) for patients with treatment-resistant depression (TRD). Methods: A systematic search (up to 25 September, 2023) of RCTs and single-arm prospective studies was conducted. Results: One RCT (n=29) and three single-arm prospective studies (n=34) met the study entry criteria. In the RCT, compared to sham, active SNT was significantly associated with higher rates of antidepressant response (85.7% versus 26.7%) and remission (78.6% versus 13.3%). Two out of the three single-arm prospective studies reported the percentage of antidepressant response after completing SNT, ranging from 83.3% (5/6) to 90.5% (19/21). In the three single-arm prospective studies, the antidepressant remission rates ranged from 66.7% (4/6) to 90.5% (19/21). No severe adverse events occurred in all the four studies. Conclusion: This systematic review found SNT significantly improved depressive symptoms in patients with TRD within 5 days, without severe adverse events.